2018
DOI: 10.1158/2326-6066.cir-17-0549
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Persistence of IL2 Signaling Enhances the Antitumor Effect of Peptide Vaccines through T-cell Expansion and Preventing PD-1 Inhibition

Abstract: Peptide vaccines can be a successful and cost-effective way of generating T-cell responses against defined tumor antigens, especially when combined with immune adjuvants such as poly-IC. However, strong immune adjuvants can induce a collateral increase in numbers of irrelevant, nonspecific T cells, which limits the effectiveness of the peptide vaccines. Here, we report that providing prolonged IL2 signaling in the form of either IL2/anti-IL2 complexes or pegylated IL2 overcomes the competitive suppressive effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…For instance, Jounaidi et al [21] reported that tethering IL-2 to its receptor significantly enhanced the antitumor and self-expansion of natural killer NK92 cells. Sultan et al [22] demonstrated that sustained persistence of IL-2 cues promoted the antitumor properties of peptide vaccines via T-cell expansion and releasing programmed cell death 1 (PD-1) blockade. Menssen et al [23] showed that both tumor necrosis factor-α and IL-2, delivered by the antibody-based method to the blood vessel in solid tumor, manifested potently immunological and antitumor effects in the syngeneic J558L BALB/c myeloma model.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Jounaidi et al [21] reported that tethering IL-2 to its receptor significantly enhanced the antitumor and self-expansion of natural killer NK92 cells. Sultan et al [22] demonstrated that sustained persistence of IL-2 cues promoted the antitumor properties of peptide vaccines via T-cell expansion and releasing programmed cell death 1 (PD-1) blockade. Menssen et al [23] showed that both tumor necrosis factor-α and IL-2, delivered by the antibody-based method to the blood vessel in solid tumor, manifested potently immunological and antitumor effects in the syngeneic J558L BALB/c myeloma model.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of heteroclitic peptides being more immunogenic than the corresponding natural sequences, clinical antitumor responses in vaccine trials have been in general suboptimal, raising doubts that tolerance can be circumvented with the use of the modified peptide vaccines. However, the results presented here and previous work by our group demonstrate that peptide vaccination using heteroclitic melanoma epitopes are effective in treating mice with established tumors, but to obtain optimal therapeutic effects (i.e., rejections), vaccination must be followed with either PD-1 blockade or sustained IL-2 administration [17,30]. Furthermore, no significant differences in the Trp1 455 CTL precursor frequencies between WT-B6 and Trp1-KO mice were observed (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…TnTR1 TCR-transnuclear mice (Trp1 455-463 specific CTLs RAG1-KO) were described [23]. Transgenic mice that express the TCR specific for gp100 [25][26][27][28][29][30][31][32][33] (pmel-1 mice) [24], or Ova 257-264 restricted TCR (OT-1 mice), were purchased from The Jackson Laboratory. Trp1-KO B6 mice were generated in our facility by breeding F1 mice of TRP-1 TCR Bw RAG-mice (Jackson Laboratory Stock No.…”
Section: Mice and Cell Linesmentioning
confidence: 99%
“…vaccination using modified palmitoylated peptides (pam-peptides) administeredin combination with a stabilized formulation of poly-IC (poly-ICLC) generates vast endogenous CTL responses in mice after 2 sequential immunizations (prime-boost, 7–12 days apart) (24, 13). Most of the T cell expansion occurs after the boost, and while priming required the use of pam-peptide, the boost can be performed using either pam-peptide or the minimal peptide (mini-peptide) epitope (2, 14). This suggests that priming requires professional antigen-presenting cells (pAPC) capable of antigen crosspresentation such as DCs (1517), whereas the boost can be mediated by either DCs (with pam-peptide) or non-professional APCs (npAPC) because the mini-peptide epitope may be presented by any MHC-I expressing cell.…”
Section: Resultsmentioning
confidence: 99%